A Comparison of Salary-Wage and Hourly-Wage Acute Care Nursing Units. (May 2015) - Hickey, Rosa G.; Buchko, Barbara L.; Coe, Paula F.; Woods, Anne B.
<x xml:space="preserve">Abstract</x> OBJECTIVE: This pilot study examined differences in RN perception of the professional practice environment and financial indicators between salary-wage and hourly-wage compensation models. BACKGROUND: There is a dearth of current information regarding use of salary-wage models for compensation for direct care nurses. METHODS: A descriptive, comparative design was used to examine the Revised Professional Practice Environment Scale (RPPE) and financial indicators of nurses in a nonprofit healthcare system over a 6-month period. RESULTS: Mean scores on the RPPE were significantly lower for hourly-wage RNs, and the hourly-wage model resulted in a 1.2% additional cost for overtime hours compared with the fixed cost of the salary-wage model. CONCLUSIONS: Nurses in an hourly-wage unit reported a significantly lower perception of the clinical practice environment than did their peers in a salary-wage unit, indicating that professional practice perceptions in a salary-wage unit may provide a more effective professional practice environment. Financial analysis resulted in a budget-neutral impact.